Antecipaç\~ao fiscal, n\~ao fundamentalidade e n\~ao causalidade no Brasil - Luan Borelli; Christian Vonbun; Geraldo Sandoval Góes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– So far, there are very few papers concerning the problems of non causality and non-fundamentalness in fiscal studies. This is even truer for Brazil. Non causality and non fundamentalness are econometric problems that are specially relevant in fiscal studies, as they are relate to fiscal foresight, a natural phenomenon in fiscal studies. Fiscal foresight is the ability, by market participants, to forecast and preview government expenditures before they effectively happen. This happens because of the legal bureaucracy that commands fiscal expenditures and tax collection. The present paper fulfills part of this gap by presenting and discussing those issues and by treating such a problem reported in Brazilian data. We estimate a non causal VAR with Brazilian typical data and compare its forecasts to a regular causal VAR, using the same data found to be non-fundamental by Vonbun and Lima (2020). The results suggest that expectations may have a role in the determination of the effects fiscal policy, as the non causal VAR has shown substantially better predictive ability than the regular causal VAR for that dataset.
Keywords: C11; C32; C53; E3; E6; E31; E62; H6; H30; 330; fiscal policy; VAR; macroeconometrics; fundamentalness; forecasting